Identification Structure Layer Land And Rock In Land Peat Use Geoelectric Method And Mechanical Test For Infrastructure Planning In Nagasaribu Village - Juliper Nainggolan; Santi Lorensa Junita Sianturi; Juniar Hutahaean (International journal of technology and education research, 2026)
Peatlands with complex physical and mechanical characteristics, such as low bearing capacity, high compressibility, and high water content, peat layers can cause problems in infrastructure planning and development. Consequently, to enable safe and sustainable infrastructure planning, a thorough study of the structure of the soil and subsurface rock layers is required. This study aims to determine the resistivity values of soil layers, rocks and soil shear strength tests in the peatlands of Nagasaribu Village and then relate them to the feasibility of infrastructure development in Nagasaribu Village. This study was carried out using the geoelectric method using the ARES-G4 v4.7 SN: 0609135 tool with a Schlumberger configuration. Furthermore, the results of the geoelectric interpretation were linked to soil mechanical test data, which include cohesion and friction angle of the peat soil. The results of the identification of soil and rock layer structures along the first, second, and third routes are dominated by Peat, Sand, Lanau Rock, Claystone, Alluvium, Sandstone, and Gravel, Shale, and Limestone. Based on the soil and rock layer structures along the first, second, and third routes, it is suitable to construct buildings according to local geological conditions. From the soil shear strength test results, soil samples from the first route fall into the very loose category, the second route into the somewhat dense category, and the third route into the very dense category. The information obtained can be used as a reference to determine the appropriate type of foundation to reduce the possibility of damage to buildings in peatland areas